A Practical Guide to Renewable Energy : Microgeneration systems and their installation - Kitcher, Chris (London : Routledge, 2012)
Learn more about renewable energy, how to install and inspect renewable energy systems and gain certification. This is a perfect introduction to one of the construction industry's leading growth areas.
Includes index.
Keywords: Electric power systems; Renewable energy sources; Small power production facilities -- Installation; Technology